2009
DOI: 10.1080/09585190902770877
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation on the factors affecting newcomers' adjustment: evidence from Japanese organizations

Abstract: Using the longitudinal survey data of newcomers working for Japanese firms, this study demonstrates that the socialization tactics used by Japanese firms were positively related to the degree of socialization of newcomers, which eventually correlated positively with the time-series differences in organizational commitment and achievement motivation from the first year (T1) to the second year (T2) of their organizational entry, and negatively with the longitudinal change in turnover intention from T1 to T2. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 54 publications
2
11
0
3
Order By: Relevance
“…SMs make heavy investments in job search (e.g., Guerrero & Rothstein, 2012; McCoy & Masuch, 2007; Sardana, Zhu, & van der Veen, 2016) and they are frequently underemployed relative to their own qualifications (Shirmohammadi et al, 2019; Syed, 2008). These characteristics lower a newcomer’s motivation to adjust to the organization (Simon, Bauer, Erdogan, & Shepherd, 2019; Takeuchi & Takeuchi, 2009). Further, the socialization of SMs may take significantly longer than the socialization of other newcomers, extending beyond the onboarding activities that employers usually deploy at organizational entry.…”
Section: Organizational Socialization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…SMs make heavy investments in job search (e.g., Guerrero & Rothstein, 2012; McCoy & Masuch, 2007; Sardana, Zhu, & van der Veen, 2016) and they are frequently underemployed relative to their own qualifications (Shirmohammadi et al, 2019; Syed, 2008). These characteristics lower a newcomer’s motivation to adjust to the organization (Simon, Bauer, Erdogan, & Shepherd, 2019; Takeuchi & Takeuchi, 2009). Further, the socialization of SMs may take significantly longer than the socialization of other newcomers, extending beyond the onboarding activities that employers usually deploy at organizational entry.…”
Section: Organizational Socialization Processmentioning
confidence: 99%
“…Lu et al (2011) found that it was a combination of high levels of English proficiency and social support from the supervisor that enabled Chinese SMs to integrate into Australian workplaces. Takeuchi and Takeuchi (2009) emphasize the importance of role modeling in the socialization process, so the SM’s line manager needs to model inclusive behavior within the work group. Indeed, our review shows that SMs are more likely to thrive in environments where their supervisors promote inclusion through empathic supervision and team development (e.g., Hoppe, Toker, Schachler, & Ziegler, 2017; van Riemsdijk et al, 2016), especially when supervisors are migrants themselves (Rajendran et al, 2017).…”
Section: The Empirical Literature On Sms: 2000-2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Cross cultural adjustment has been found to be positively related to performance on the assignment and negatively related to the premature termination of the assignment (Black, 1988;Caligiuri, 1997) and as a result researchers have examined a variety of factors which might influence and predict increased adjustment. In practice, the general belief has been that an expatriate that is successful in one assignment is more likely to be successful in another, regardless of the destination (Takeuchi & Takeuchi, 2009). The expatriate will have gained experience in intercultural communication, relocation, and cognitive skills, all of which should have a positive influence on the expatriates' cross-cultural adjustment in the new location (Black, Mendenhall, & Oddou, 1991;Selmer, 2002;Shaffer, Harrison, & Gilley, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Institutionalized tactics are collective, formal, sequential, fixed, serial, and investiture, as opposed to individualized tactics that are individual, informal, random, variable, disjunctive, and divestiture. Previous studies have found that institutionalized tactics (Jones, 1986) were positively related to a large number of outcome variables including job satisfaction and organizational commitment (e.g., Ashforth, Sluss, & Saks, 2007;Saks et al, 2007;Takeuchi & Takeuchi, 2009). Six dimensions are used to characterize socialization tactics, that can be grouped into three categories that include context, content, and social tactics (Jones, 1986).…”
mentioning
confidence: 99%